The Effect of Cool-Down and Relaxation Exercises on Lactic Acid Concentration and the Dribbling and Passing Skills of Advanced Football Players (Texas Journal of Multidisciplinary Studies, 2024)
The research focused on the following objectives: • the impact of relaxation and cool-down techniques on lactic acid levels as well as advanced football players' dribbling and passing abilities. • the variations in the lactic acid concentration post-tests and the advanced football players' dribbling and passing abilities between the experimental and control groups. To achieve the study's objectives, the researcher hypothesized: • There are statistically significant differences in lactic acid concentration and the dribbling and passing skills of advanced football players. • There are statistically significant differences between the post-test results of the experimental and control groups in lactic acid concentration and the dribbling and passing skills of advanced football players